ANALISIS FILM “THE BATMAN”: ISU SOSIAL DAN PEMERINTAHAN DI KOTA GOTHAM - Ajeng Ayu Milanti (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2023)
Abstract This article examines social and governmental issues in the film "The Batman". The film "The Batman" which will be released on March 2 2022 tells the story of Batman who becomes a reliable vigilante and detective in uncovering criminals in Gotham City. The method used in analyzing this film is a descriptive qualitative method. At the analysis stage, first the short story/synopsis, plot and characters in the film are examined. Next, the story in the film is analyzed in the form of issues of a dilapidated government system, issues of social inequality, rampant crime, and officials who behave in a corrupt and immoral manner. The Batman film is a depiction of the reality of social and government issues as well as a satire on real life depicted through films. Abstrak Artikel ini mengkaji isu sosial dan pemerintahan dalam film “The Batman”. Film "The Batman" yang rilis pada tanggal 2 Maret 2022 menceritakan seorang Batman yang menjadi vigilante dan detektif andal dalam mengungkap penjahat-penjahat di Kota Gotham. Metode yang dipakai dalam analisis film ini adalah metode kualitatif deskriptif. Pada tahap analisis, pertama diteliti cerita singkat/sinopsis, alur, serta karakter pada film. Selanjutnya, dianalisis cerita di dalam film berupa adanya isu bobroknya sistem pemerintahan, isu ketimpangan sosial, kejahatan yang merajalela, dan pejabat yang berperilaku korup dan amoral. Film The Batman merupakan gambaran realitas dari isu sosial dan pemerintahan serta sindiran terhadap kehidupan nyata yang digambarkan melalui karya film.